Monitoring agricultural plantations with remote sensing imagery - Camelia Slave; Anca Rotman (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
In agriculture, a major benefit of satellite registrations crop is forecast problem by following up the development of crops in certain phenological stages. Then, the registration of pest attacks made possible intervention in the early stages of this phenomenon. Development of the Earth's surface registration techniques in different spectral bands, specialized for certain components of the environment. Such as those of the last LANDSAT and SPOT satellites were able to follow some aspects of forestry and agriculture.
Keywords: 330; Agriculture; agricultural plantations remote sensing spectral bands; vegetation